WORKING AIDS DESIGN BY USING 5-STEP METHOD BASED ON REBA AND RULA ANALYSIS TO REDUCE THE RISK OF LOW-BACK PAIN INJURY A Case Study in Brickworks Center in Potorono, Banguntapan, Bantul - Wahyu Sidiq Saputra; Trio Yonathan Teja Kusuma (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2020)
Brickworks Center in Potorono is the center of brickworks which is quite large in Bantul and produces high amount of both raw bricks, which has not been burned yet, and the mature bricks, or the burned one. Manual material handling work on the activity of brick production has high risk of causing spinal injury (low-back pain). This research aims to analyze the activity of material handling work by using Rapid Entire Body Assessment and Rapid Upper Limb Assessment approaches and also create design proposal by using 5-Step Method of Concept Designing to design working aids which can applied to improve working posture. From the data assessment and analysis, the result of Rapod Entire Body Assessment score on the first posture is 9, second posture is 4, third posture is 8, fourth posture is 5 and the score of Rapid Upper Limb Assessment is all 7, which in general, those scores are potential to have high risk of low-back pain so that it needs improvement of working postures. The improvement of working posture has carried out by creating Roller Conveyor Modification to reduce the risk of low-back pain injury. The final result after improvement has been carried out is the score of Rapid Entire Body Assessment is 1 and the score of Rapid Upper Limb Assessment is 3, which show decreasing score.